Mycosis Fungoides Palmaris et Plantaris Progressing to Complete Early-Stage Disease Improved with Phototherapy - Tina Elaine M. Resuello; Jacqueline Michelle D. Melendres; Mary Elizabeth S Danga; Patricia Anne T Tinio (European Medical Journal, 2023)
Mycosis fungoides is the most common form of cutaneous T cell lymphoma. In this article, the authors describe a case of a 53-year-old female who presented with multiple pruritic, slightly erythematous and hyperpigmented, variably shaped macules, and patches and plaques, with scaling on the bilateral hands and feet. The lesions resembled various benign inflammatory dermatoses, such as contact dermatitis and superficial dermatophytosis, and were treated as such until hyperpigmented, variably shaped macules and patches appeared on the legs and with a bathing trunk distribution. Histopathologic and immunohistochemical findings were consistent with early mycosis fungoides. The patient has improved with full body narrowband ultraviolet B phototherapy, combined with a psoralen ultraviolet A soak for the hands and feet. This case highlights the importance for physicians to recognise that mycosis fungoides may occur with different presentations, and may not present in its classic form. The patient's quality of life may be improved with early diagnosis.